What is the diet of Palaemon elegans Rathke, 1837 (Crustacea, Decapoda), a non-indigenous species in the Gulf of Gdańsk (southern Baltic Sea)? - Urszula Janas (Oceanologia, 2008)
Palaemon elegans, a new component of the Gulf of Gdańsk macrozoobenthos,colonised the southern Baltic coastal zone in the late 20th and early 21stcentury. Analysis of the stomach contents of P. elegans revealed 16plant and animal taxa that these prawns had fed on. The principal dietarycomponent was detritus, with a mean frequency of occurrence in stomachs of > 80%.The most frequently occurring plant components in the diet were algaefrom the genus Cladophora and the family Ectocarpaceae, while the mostsignificant animal components were Harpacticoida, Chironomidae, Ostracoda andGammarus spp. The results of the study show that the dietary composition ofP. elegans differed significantly between stations and months. The foraging area consisted of two distinctive regions - the Inner Puck Bay, and the Outer Puck Bay together with the Dead Vistula River; two of the stations - Gdynia and Sopot - were distinctfrom all the others. However, no obvious seasonality in the food compositioncould be demonstrated.